Réponses

2013-09-02T20:07:18+02:00
45)
A=5(x-1)²-3(x-1)

A=(x-1)[5(x-1)-3]
A=(x-1)(5x-8)

B=x²-9-(x-3)(5x+2)
B=(x-3)(x+3)-(x-3)(5x+2)
B=(x-3)[(x-3)-(5x+2)]
B=(x-3)(x+3-5x-2)
B=(x-3)(-4x+1)

46)
A=2(2x-1)²-5(2x-1)
A=(2x-1)(2-5)
A=(2x-1)(-3)
B=(3x-1)(3x+1)+2(3x-1)(x-4)
B=(3x-1)(3x+1)+2(x-4)

47)
A=4(x+3)²-(x-3)(x+3)
A=(x+3)[4(x+3)-(x-3)]
A=(x+3)[4x+12-x+3)=(x+3)(3x+15)

B=(4-3x)(4+3x)+2(4+3x)²
B=(4+3x)[(4-3x+2(4+3x)]
B=(4+3x)(12+3x)
B=(4+3x)3(4+x)
B=3(4+3x)(4+x)

48)
A=x²(x+1)+(x+1)
A=(x+1)(x²+1)

B=x²(x-1)+(x-1)
B=(x-1)(x²+1)